The People Who Occupied The Fallen Angels' Chairs in Heaven: A Reiterated Idea in the Fifteenth Century, the Valencian Golden Age. Issue 7 (July 2018) - RAMOS, MARCO ANTONIO CORONEL
Abstract : Johannes Ludovicus Vives (1493–1540) repeatedly used the symbolic image of humans occupying the fallen angels' chairs in heaven. In fact, the purpose of the creation of human beings seemed to be to occupy those empty chairs in paradise. This article focuses on the recurrent presence of that idea in the Valencian literature of the fifteenth century. It was a thought that was widely accepted even among people of a limited educational background. This paper supports the idea that Vives was the scholar who took this well-known belief from his homeland and introduced his Erasmian circle to it. That process of dissemination is described and explained by quoting some fragments of the most important Valencian authors of that time and other, representative, members of Spanish Erasmism.